Theories of personality - Hall, Calvin S. (Calvin Springer) 1909-1985; Lindzey, Gardner (John Wiley & Sons, Inc., 1970)
Covers personality theories of Sigmund Freud (psychoanalytic theory), C.G. Jung (analytic theory), Henry A. Murray (personology), Kurt Lewin (field theory), Gordon Allport, William H. Sheldon (constitutional theory), Raymond B. Cattell (factor theory), B.F. Skinner (operant reinforcement theory), Carl Rogers (self theory); also, social psychological theories, organismic theory, stimulus-response theory, existential psychology.